A Novel Approach to Monitoring the Performance of Carbon-Fiber-Reinforced Polymer Retrofitting in Reinforced Concrete Beam–Column Joints - Sapidis, George M.; Naoum, Maria C.; Papadopoulos, Nikos A.; Golias, Emmanouil; Karayannis, Chris G.; Chalioris, Constantin E. (Applied sciences, 2024)
Due to insufficient transverse reinforcement, the retrofitting of beam–column joints (BCJs) in existing reinforced concrete (RC) frame structures is commonly required to alter their brittle behavior. The construction industry has extensively embraced carbon-fiber-reinforced polymers (C-FRPs) as near-surface-mounted (NSM) reinforcement. Monitoring the performance of C-FRP retrofitting is crucial due to the wide range of factors influencing its effectiveness. A novel methodology has been implemented to assess the efficacy of the C-FRP retrofitting method in this study. This approach was validated through experimental investigation of full-scale BCJs, which were retrofitted with C-FRP ropes and subjected to cyclic loading. Furthermore, piezoelectric lead zirconate titanate (PZT) patches were placed on the NSM C-FRP ropes, and the electro-mechanical impedance (EMI) method was employed to monitor the retrofitting technique’s performance. A combination of the commonly used statistical damage index root mean squared deviation (RMSD) and a hierarchical clustering-based approach (HCA) was used to assess the performance of the C-FRP retrofitting technique. The experimental investigation results strongly indicate the proposed approach’s positive impact on the reliable assessment of C-FRP retrofitting performance. Thus, the proposed approach enhances the safety and resilience of retrofitted BCJs in RC structures.